Vagus Nerve Injury during Continuous Intraoperative Neuromonitoring (cIONM) for Thyroid Surgery: Assessment of Severity - Muhammad, Rohaizak; Abdullah Suhaimi, Shahrun Niza; Abdul Rashid, Nor Faezan; Othman, Suraya (IIUM Medical Journal Malaysia, 2021)
Introduction: Vocal cord palsy is one of the biggest concern in thyroid surgery especially among the professional voice user. Continuous intra-operative nerve monitoring allows real time of the nerve function during surgery that will reduce risk of injury. The procedure involve is not without complication but meticulous usage and following standard operating procedure is utmost important. This study was aimed looking at the potential morbidity of the procedure. Methodology: A prospective observational study was conducted on 20 patients who underwent routine thyroid surgery using c-IONM. The procedure of c-IONM follows the standard guidelines. Measurements of vagal stimulation were taken proximal(V3) and distal(V2) to APS electrode to document any injury to the vagus nerve. The blood pressure and pulse rate were also documented through-out surgery, looking at the physiological effect of the stimulation. The function of the vocal cord was assessed by pre and post-operative laryngoscopy Result: 18 patients with 29 nerves at risk were included as in two patients, the vagal stimulation did not achieve the acceptable amplitude (400 µV). There were drops of amplitude between V3 and V2 in 14 nerve at risks but there was clinical evidence of palsy on laryngoscopy. There were also fluctuation of mean arterial pressure and pulse rate but not significant enough to warrant intervention. Conclusion: The use of c-IONM during thyroidectomy do exert minimal effect on the vagus nerve and its function but not significant enough to abandoned the procedure. It is safe and able to help the surgeon to identify and preserve the nerve function especially in difficult thyroidectomy